Neuromuscular training effects on athletes` jumping and lower limb injury: a systematic review - Qin, Z.; Qin, Y.; Wang, J. (Journal of Motor Behavior, 2024)
This study assessed the impact of integrated neuromuscular training (INT) on athletes` jumping performance and lower limb injury prevention. A thorough search across multiple databases, including PubMed, Web of Science, Science Direct, and the Cochrane Library, identified a sample of 19,805 athletes aged between 8.5 and 27.7 years. Results showed that INT led to a significant improvement in jumping ability (SMD = 0.45, 95% CI 0.30-0.60, P = 0.000) and a reduction in lower limb injuries (SMD = 0.68, 95% CI 0.62-0.74, P = 0.000). The most effective interventions lasted at least 25 minutes, conducted 2-5 times per week, for a minimum of 9 weeks. This approach was particularly beneficial for children and adolescents, as it enhanced their countermovement jump (CMJ) ability and helped in the prevention of injuries.